Legal Due to Local Distribution Towards Land Registration Rights in Ogan Komering Ulu District (Jurnal Bina Praja, 2021)
The local expansion was a concrete manifestation of local autonomy. In addition, regional expansion is splitting from one region to more than one region to support community welfare. The problems discussed in this study were the consequences of the law of local expansion on the registration of land rights in Ogan Komering Ulu district and solutions to resolve land conflicts due to the expansion of the area. This study uses a normative juridical approach where the literature used is regulations and books. In conclusions, the legal consequences of the division of Ogan Komering Ulu District on the implementation of land registration indicate a change in the work area and authority for making land deeds by the Land Deed Making Officials and changes in the work area and authority in carrying out the duties and obligations of registering land at the Land Office of Ogan Komering Ulu district. To solve this conflict problem, the Ministry of Home Affairs sometimes must intervene in the dispute resolution process. Conflicts like this can hinder the wheels of government in the regions. Another solution is for the government to immediately finalize the grand design while still paying close attention to historical aspects and customs before many conflicts occur in the regions.
Keywords: Local Expansion; Land Conflict; Land Rights